IMPROVEMENT OF MECHANISMS FOR ORGANIZING PHYSICAL EDUCATION CLASSES OF GENERAL SECONDARY SCHOOLS ON THE BASIS OF A PROJECT APPROACH - I. Q. Shamsieva (American Journals, 2023)
This graduation work is about physical education lessons in high sport school is to teach students about the physical attributes to the introduction of innovative technologies aimed at the development of modern methods of teaching movement, the general classification of the essence, the concept of vision. Physical education theory and methodology of noise that can be used in educational technology in teaching students how to study the concept. Final work of students in the physical qualities of positive effects on the body.
Keywords: Competitions, standard of exercises, load, quality, general development, cyclic, acyclic, practical, oral, indicative, methods.